Pro SQL Server 2008 Administration - Simmons, Ken; Carstarphen, Sylvester (Apress : Imprint: Apress, 2009)
Pro SQL Server 2008 Administration is critical for database administrators seeking in-depth knowledge on administering SQL Server 2008. This book covers the impact of the new features available in SQL Server 2008 specifically targeted for database administrators, along with the tried-and-true advanced techniques required to support and maintain Microsoft SQL Server. Introduces new administration features of SQL Server 2008 Shows how to manage a SQL Server 2008 database at professional level Provides guidance on performance optimization.